2010
DOI: 10.1111/j.1537-2995.2010.02873.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of additive solutions and pathogen inactivation treatment of platelet components in a regional blood center: impact on patient outcomes and component utilization during a 3‐year period

Abstract: Universal use of PI was implemented without impacting component use, as indicated by total dose of PLTs per patient, and outcomes to transfusion were improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 13 publications
5
80
0
5
Order By: Relevance
“…Detailed haemovigilance and post marketing surveillance in Europe since 2003 continues to demonstrate safety and efficacy of the treated products. [54][55][56][57][58] Although high levels of inactivation have been demonstrated for a number of viruses including single-stranded RNA viruses, 38,40 the efficacy of amotosalen and UVA treatment of inactivation of high CHIKV doses had not been tested. Here, we describe the successful inactivation of high doses of CHIKV in apheresis platelet concentrates and plasma components using the amotosalen and UVA treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed haemovigilance and post marketing surveillance in Europe since 2003 continues to demonstrate safety and efficacy of the treated products. [54][55][56][57][58] Although high levels of inactivation have been demonstrated for a number of viruses including single-stranded RNA viruses, 38,40 the efficacy of amotosalen and UVA treatment of inactivation of high CHIKV doses had not been tested. Here, we describe the successful inactivation of high doses of CHIKV in apheresis platelet concentrates and plasma components using the amotosalen and UVA treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Experience has shown that clinical benefits after introduction of IBS are the reduction of allergic-type ATRs and the prevention of ATRs caused by bacteria in PCs [10,25]. So far no German studies are available on ATR rates subsequent to transfusion of IBS-treated platelets.…”
Section: Methodsmentioning
confidence: 99%
“…This data was derived from a French study comprising mainly haematology/oncology patients. Without IBS 5.3 % and with IBS 1.4 % ATRs were reported [25]. To determine treatment costs of the clinical symptoms of ATRs, these possible reactions were allocated to grade 1-3 reactions according to the WHO (grade 1: absence of immediate or long-term vital threat; grade 2: long-term morbidity; grade 3: immediate vital threat; grade 4: death of the patient) [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…The IPTAS data are in contrast to a larger, successfully completed, randomized controlled study and a meta-analysis of nine studies 2 that showed no increase in at least Grade 2 bleeding or the need for more RBC transfusion support with the use of INTERCEPTtreated PLTs, as well as the real-world, pragmatic published experience of three independent European clinical centers that demonstrates no increase in PLT, RBC, or plasma usage with the introduction of INTERCEPT-treated PLTs in routine use. 3,4 Indeed, even in massively transfused patients, no increase in the need for PLT, RBC, or plasma transfusion support; in-hospital mortality; or length of stay was experienced with INTERCEPT-treated PLTs. 5 Based on an unbalanced, prematurely terminated, underpowered study, Rebulla and coworkers state that "the study provides additional information on the safety and efficacy of pathogen-reduced PLTs treated with two commercial pathogen-reduction technologies" and imply that the data indicate increased utilization of PLTs and RBCs in INTERCEPT pathogen-reduced PC recipients.…”
mentioning
confidence: 99%